2016
DOI: 10.3945/ajcn.116.130716
|View full text |Cite
|
Sign up to set email alerts
|

Relation between mealtime distribution of protein intake and lean mass loss in free-living older adults of the NuAge study

Abstract: Our results suggest that greater protein intakes and a more even distribution across meals are modifiable factors associated with higher muscle mass in older adults but not with losses over 2 y. Interventional studies should determine longer-term effects on preserving LM with aging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
110
2
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 118 publications
(125 citation statements)
references
References 49 publications
12
110
2
1
Order By: Relevance
“…We recently showed that an even distribution of protein intake, independent of its quantity, was associated with a higher muscle mass in NuAge study participants (11). This result led us to hypothesize that the mealtime distribution of protein intake may also be important in preserving muscle strength and mobility in TABLE 5 Repeated multivariate analysis of changes in mobility score and protein distribution older adults who are at the greatest risk of functional decline (45,46).…”
Section: Protein-intake Distribution and Physical Performancementioning
confidence: 99%
See 4 more Smart Citations
“…We recently showed that an even distribution of protein intake, independent of its quantity, was associated with a higher muscle mass in NuAge study participants (11). This result led us to hypothesize that the mealtime distribution of protein intake may also be important in preserving muscle strength and mobility in TABLE 5 Repeated multivariate analysis of changes in mobility score and protein distribution older adults who are at the greatest risk of functional decline (45,46).…”
Section: Protein-intake Distribution and Physical Performancementioning
confidence: 99%
“…In brief, the protein CV for each subject was calculated as the SD divided by the mean where the SD was the SD of grams of protein per meal (excluding snacks), the mean was the mean grams of protein per day. Lower protein CV values reflected the evenness of protein intake across breakfast, lunch, and dinner (11,43).…”
Section: Statistical Analysesmentioning
confidence: 99%
See 3 more Smart Citations